Nanoscopic yttrium oxide fluorides: non-aqueous fluorolytic sol–gel synthesis and structural insights by 19F and 89Y MAS NMR1. Issue 30 (14th August 2015) - Scholz, G.; Dreger, M.; Bertram, R.; Kemnitz, E.
<x xml:space="preserve">Abstract</x> Nanoscopic yttrium acetate fluorides Y(CH3COO)3−zFz and yttrium oxide fluorides YO(3−z)/2Fz were prepared via the fluorolytic sol–gel route and studied by 19F and 89Y MAS NMR.